CHANGES IN HUMAN RESOURCES MANAGEMENT IN A PANDEMIC (FOR THE RESULTS OF NARRATIVE EXPERT INTERVIEWS) - Приступа, М. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2021)
The article is dedicated to the analysis of the changes in HR management practices in Ukrainian enterprises during the pandemic. Introduction of the anti-epidemic restrictions has a large impact on market situation, and labor market in particular, creating a critical situation for enterprises. In such situation new challenges in HR management emerge, which, have being solved successfully, will allow mitigating the consequences of the pandemic for enterprises and workers. Since such conditions are completely novel, there is a lack of the systemic research of the factors that influence managerial decision-making. The article is aimed at the identification and analysis of the most significant challenges emerging in the area of HR management due to the epidemic hazard spread and the introduction of the anti-epidemic restrictions. The research is based on the results of the expert interview with different level managers of the private and state enterprises operating in the areas of education, science, IT, finance and service. Data reveal that the most problematic challenge was the transition to remote work leading to the technical, psychological, and methodical difficulties in the work performance. Moreover, the different level of availability of the remote work in different enterprises and areas conditions unequal influence made by the crisis on workers and the intensification of socioeconomic inequalities. Another important aspect is the informal relationships management and the integration of workers, since consolidated work groups appear more resistant toward the stress of the abrupt changes in working conditions. The situation of uncertainty regarding the future development of the pandemic and the introduction of anti-epidemic measures shortens the strategic planning perspective and bears high conflict potential, which will complicate labor market recession. It is suggested to use the presented results for the further detailed and systemic research of the influence made by the pandemic on the changes in HR management practices in the context of the global transformations of labor relationships.